Tinjauan Farmakologis Trihexyphenidyl dan Penyalahgunaan di Komunitas - Putri Athira Tarigan (Lembaga Pengembangan Kinerja Dosen, 2025)
Trihexyphenidyl (THP) is a type of anticholinergic drug. The anticholinergic side effects of trihexyphenidyl drugs are categorized as peripheral or central. Common peripheral side effects are dry mouth, lack of sweating, decreased bronchial secretions, blurred vision, difficulty urinating, constipation and tachycardia. Central side effects of anticholinergics include impaired concentration, attention and memory. Drug abuse is the use of drugs (e.g., pain relievers, tranquilizers, stimulants, sedatives, etc.) and over-the-counter drugs (e.g., loperamide, promethazine, antitussive cough syrup, etc.) for purposes other than medical for the purpose of pleasure, resulting in dependence, physical damage, psyche and even death. It has recently been revealed that trihexyphenidyl (THP) is one type of drug that is often abused. the prevalence of anticholinergic abuse is 34%, and trihexyphenidyl is the most commonly involved anticholinergic due to its tendency to produce a “high”.